An assessment of the factors influencing household willingness to pay for non-marketed benefit of cattle in the agro-pastoral systems of Mozambique - Ng'ang'a, K.; Ritho, C.; Nzuma, J.; Moyo, Siboniso; Herrero, Mario (Academic Journals, 2013)
This study used Probit model to analyze factors influencing probability of household willingness to pay for non-marketed benefits (NBS) of cattle in Mozambique. The primary data from 184 agro-pastoralist households were collected using a structured questionnaire. Data collected comprised information relating to household demographic, household livelihoods and non-marketed benefits of cattle. The result showed that the probability of household willingness to pay (WTP) was influenced by both animal and household related characteristics. Animal related characteristics that had a significant influence on the probability of households WTP for NMB’s of cattle included: Animal age (ANAGE), herd size (HERDSIZE) and cattle breeds (INDBRED). Household related characteristics that had significant (p<0.05) influence on probability of household WTP for NMB’s of cattle, comprised: Dependant ratio (DEPRAT), household size (HHS), off-farm income (OFFINC) and distance to the market (DISTMK). As expected, however, the OFFINC had a negative influence on probability of household WTP for NMB’s of cattle. The study concluded that non-marketed benefits of cattle were highly valued among agro-pastoralist in Mabalane district and thus were willing to pay for them.